Characterisation of fatigue damage in composites using an Acoustic Emission Parameter Correction Technique. (15th October 2018) - Al-Jumaili, Safaa Kh; Eaton, Mark J.; Holford, Karen M.; Pearson, Matthew R.; Crivelli, Davide; Pullin, Rhys
Abstract: In industrial applications of composite materials, accurate characterisation of damage is vital. Acoustic Emission (AE) can be utilised to achieve this, however, in large-scale complex geometry components, traditional AE approaches have limitations. In this study a large carbon fibre specimen was used to generate different damage mechanisms under fatigue loading. The Delta T Mapping technique was used to locate damage and signal features were corrected using the Parameter Correction Technique (PCT). A comparison between results obtained using traditional signal features and those obtained using PCT is given. The results are validated using C-scanning and computed tomography. Matrix cracking and delamination were successfully identified using the PCT approach and improved location accuracy was achieved.